Effectiveness of PADIDA intervention strategies through the application of the two-armed star test aimed at strengthening attentional skills in university students. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2022)
INTRODUCTION: The present research aims to communicate the effectiveness of the PADIDA intervention strategies through the application of the two-arm star test, oriented towards the strengthening of attentional skills in students of the Academic Program of Psychology at the University of Santander METHODS: The research approach is quantitative, with a pre-experimental design, applying the PADIDA intervention strategies. The scope is comparative, of longitudinal type. The type of sampling is non-probabilistic and the population to be studied is made up of five (5) university students. RESULTS: According to the results of the pretest, it is evident that, with respect to the duration, the average time used for the execution of the test is 55.025 seconds and, in relation to the number of errors, the average is 1.85, this in order to establish a benchmark with respect to the evaluation to be performed after the interventions. After the interventions, it was obtained as a result that, regarding the duration, a decrease in the time used was evidenced, because the average time was 41.3 seconds and, in relation to the number of errors the average corresponds to 0.5, therefore, a remarkable decrease is observed when comparing the initial and final averages, however, if we take into account what was obtained in the hypotheses, these results are not statistically significant between the initial and final evaluation.ANALYSIS AND DISCUSSION: Attention can be defined as a neuropsychological function of the human being, which has several subprocesses such as focalization, selectivity, sustainability, division and alternation (25), in other words, it is the ability to select and concentrate on relevant stimuli (1). When analyzing the results obtained from the pre- and post-test by means of the two-arm star test that evaluates attention, performance and concentration capacity, it was found that no significant differences were observed between these evaluations in relation to the application of the PADIDA interventions; however, it is worth noting that there are improvements in terms of the reduction of the time applied to perform the test and the number of errors.CONCLUSIONS: Regarding the results that were obtained and, taking into account the hypothesis statement, it was evidenced that no significant differences were found between the initial and final evaluation, however, it is possible to observe some improvement, In order for this improvement to be significant and demonstrate greater effectiveness of the PADIDA intervention strategies, it is suggested to apply the activities more frequently, likewise, it is recommended that they not only be carried out by a group of researchers but that they can be implemented both in classrooms and at home.
Keywords: two-armed star; attention; selective attention; sustained attention; divided attention